2018
DOI: 10.1111/nyas.13610
|View full text |Cite
|
Sign up to set email alerts
|

Evolving building blocks of rhythm: how human cognition creates music via cultural transmission

Abstract: Why does musical rhythm have the structure it does? Musical rhythm, in all its cross-cultural diversity, exhibits commonalities across world cultures. Traditionally, music research has been split into two fields. Some scientists focused on musicality, namely the human biocognitive predispositions for music, with an emphasis on cross-cultural similarities. Other scholars investigated music, seen as a cultural product, focusing on the variation in world musical cultures. Recent experiments found deep connections… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Iterated learning experiments have been done to better understand linguistic morphology, poetry, and musical rhythm . − Iterated learning experiments where participants imitate and transmit nonsense syllable sequences could be used to show whether, and if so how, cultural transmission amplifies domain‐general biases resulting in rhythmic patterns of speech. This iterated learning approach can be integrated with neurophysiological measures .…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Iterated learning experiments have been done to better understand linguistic morphology, poetry, and musical rhythm . − Iterated learning experiments where participants imitate and transmit nonsense syllable sequences could be used to show whether, and if so how, cultural transmission amplifies domain‐general biases resulting in rhythmic patterns of speech. This iterated learning approach can be integrated with neurophysiological measures .…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Lacking a time machine to directly witness early human evolution, a comparative approach is key to understanding how rhythm processing evolved in our species [4,[55][56][57][58][59]. Comparisons within humans between cognitive domains, individuals, cultures, and developmental stages are illuminating [60][61][62][63][64], but cross-species comparisons can highlight which behavioral features and neural systems are crucial for a species to develop rhythmic competence and can help reconstruct both when and why these features or systems evolved. The presence or absence of features of rhythmic competence in other animals can be mapped to evolutionary gains (or losses) of the sub-components underlying modern human rhythmicity.…”
Section: Animal Rhythmicity: a Comparative Approachmentioning
confidence: 99%
“…Moreover, there are already some experimental results suggesting that single participants simply do not follow the same trajectories as traditions with multiple individuals. For instance, Claidière et al [47] have found, in a transmission chain with baboons, a higher performance and transmission fidelity in traditions with multiple participants than in individuals presented with their own earlier outputs (but see [78]).…”
Section: (B) Using Design Spacesmentioning
confidence: 99%